2018
DOI: 10.1002/jcp.27990
|View full text |Cite
|
Sign up to set email alerts
|

The role of microRNAs in embryonic stem cell and induced pluripotent stem cell differentiation in male germ cells

Abstract: New perspectives have been opened by advances in stem cell research for reproductive and regenerative medicine. Several different cell types can be differentiated from stem cells (SCs) under suitable in vitro and in vivo conditions. The differentiation of SCs into male germ cells has been reported by many groups. Due to their unlimited pluripotency and self‐renewal, embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSCs) can be used as valuable tools for drug delivery, disease modeling, developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 114 publications
0
9
0
Order By: Relevance
“…miRNAs are small noncoding RNAs that are evolutionarily conserved, and they regulate gene expression at the posttranscriptional level by interacting with the 3'UTR of mRNAs and recruiting molecular machinery that degrades the target mRNAs (22). Research on miRNAs is currently of great importance in species ranging from plants (23) to humans, especially in the fields of ontogeny (24), cancer (25), and inflammation (26,27). In recent years, many studies have contributed to the discovery of novel miRNAs; although these works were intended to shed light on the regulatory roles of these molecules, the confirmation of miRNA-mRNA target pairs has mainly been accomplished based upon interaction or expression patterns but not functional targeting (28).…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs are small noncoding RNAs that are evolutionarily conserved, and they regulate gene expression at the posttranscriptional level by interacting with the 3'UTR of mRNAs and recruiting molecular machinery that degrades the target mRNAs (22). Research on miRNAs is currently of great importance in species ranging from plants (23) to humans, especially in the fields of ontogeny (24), cancer (25), and inflammation (26,27). In recent years, many studies have contributed to the discovery of novel miRNAs; although these works were intended to shed light on the regulatory roles of these molecules, the confirmation of miRNA-mRNA target pairs has mainly been accomplished based upon interaction or expression patterns but not functional targeting (28).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, miRNAs can modulate/deregulate the expression and functioning of genes and their products associated with the signaling pathways which are integral for the maintenance, growth, and function of CSCs such as Wnt/β-catenin, Notch, and others [50]. It has now become evident that miRNAs play a vital role in various developmental and regulatory mechanisms of stem cells such as maintenance, reprogramming, pluripotency, and differentiation by targeting various differentiation pathways, and thus, the overall regulatory action of miRNAs on stem cells suggests a critical role of miRNAs in the development of mammals [2,51].…”
Section: Role Of Mirna and Oncogenic Signaling Pathways In Human Cancmentioning
confidence: 99%
“…reprogramming, pluripotency, and differentiation by targeting various differentiation pathways, and thus, the overall regulatory action of miRNAs on stem cells suggests a critical role of miRNAs in the development of mammals [2,51]. Initially, it was the discovery of let-7 and lin-4 miRNA in Caenorhabditis elegans which revealed that miRNAs play a significant role in regulating the various molecular mechanisms related to the embryonic development and function of stem cells in mammals.…”
Section: Role Of Mirna and Oncogenic Signaling Pathways In Human Cancmentioning
confidence: 99%
“…The aberrant expression of microRNAs leads to various cancers [6,7]. MicroRNAs regulate the development of cancers, such as migration, apoptosis, proliferation and differentiation [8][9][10]. MiR-301a-3p expresses in many tissues, which belongs to miR-301 family.…”
Section: Introductionmentioning
confidence: 99%